Regional land use schemes generated by TOPAZ - Dickey, J.W.; Najafi, F.T. (Regional studies, 1973)
Dickey J. W. and Najafi F. T. (1973) Regional land use schemes generated by TOPAZ, Reg. Studies 7, 373-386. TOPAZ, which is the Technique for the Optimal Placement of Activities in Zones, was developed to provide the urban planner with a series of alternative solutions from which he could determine the land use pattern with the least amount of cost involved. In line with this objective, TOPAZ was applied to the New River Valley Planning District. The District was divided into 40 zones and five activities-residential, commercial, public/semi-public, industrial, and recreational-were investigated. Cost information for land, building units, and utilities was obtained for all activities. A constant cost of travel was assumed. Regional land use and transportation data were developed and utilized in the computer programme. The TOPAZ generated several alternative solutions with maximum and minimum costs of travel, buildings, utilities, access facilities, and so on. The resulting land use patterns were compared with each other and with a feasible solution developed by the District staff. The aim of this comparative effort was to generate other low cost solutions implicitly incorporating certain social and political factors. The technique proved to be a beneficial aid to the planning profession and generated alternative courses of action with a relatively small computer time of about 2 minutes on the IBM 360/65.